Allopatric humpback whales of differing generations share call types between foraging and wintering grounds - Mikala V. Epp (Nature Portfolio, 2021)
Abstract Humpback whales (Megaptera novaeangliae) are a cosmopolitan baleen whale species with geographically isolated lineages. Despite last sharing an ancestor ~ 2–3 million years ago, Atlantic and Pacific foraging populations share five call types. Whether these call types are also shared between allopatric breeding and foraging populations is unclear, but would provide further evidence that some call types are ubiquitous and fixed. We investigated whether these five call types were present on a contemporary foraging ground (Newfoundland, 2015–2016) and a historic breeding ground (Hawaii, 1981–1982). Calls were classified using aural/visual (AV) characteristics; 16 relevant acoustic variables were measured and a Principal Component Analysis (PCA) was used to examine within-call and between-population variation. To assess whether between-population variation influenced classification, all 16 variables were included in classification and regression tree (CART) and random forest analyses (RF). All five call types were identified in both populations. Between-population variation in combined acoustic variables (PC1, PC2, PC3) was lower within call types than among call types, and high agreement between AV and quantitative classification (CART: 83% agreement; RF: 77% agreement) suggested that acoustic characteristics were more similar within than among call types. Findings indicate that these five call types are shared across allopatric populations, generations, and behavioural contexts.